A Survey on 5G Network Slicing Enabling the Smart Grid - xia, Xu; Zhang, Lei; Mei, Chengli; Li, Jinyan; Zhu, xuetian; Liang, Yun; Song, Jeffrey (2019 IEEE 25th International Conference on Parallel and Distributed Systems (ICPADS), 2019)
In recent years, the State Grid Corporation of China (SGCC) has been building a strong smart grid to improve the security level of the power grid. By implementing the Internet+ strategy, the SGCC comprehensively improves the informatization and intelligence of the power grid and fully utilizes modern information communication technologies and control technologies. Network slicing is not only a technology but also a new business model, which has attracted broad interest of researchers. Base on above background, in this paper, several typical user cases for smart grid are introduced firstly. In addition, we present the E2E business models and steps to implement network slicing for operators. Besides, the Total Cost of Ownership (TCO) and Return on Investment (ROI) of Network Slicing are also analyzed in Smart Grids for Operators